Examination of the relationship between disease activity and patient‐reported outcome measures in an inflammatory bowel disease cohort. Issue 10 (4th October 2018) - Jackson, Belinda D.; Con, Danny; Gorelik, Alexandra; Liew, Danny; Knowles, Simon; De Cruz, Peter
Abstract: Background: The extent to which disease activity impacts patient‐reported outcomes (PRO) is unclear. Aims: To examine the relationship between disease activity and PRO. Methods: Adult inflammatory bowel disease (IBD) patients attending a tertiary clinic from May to June 2015 were included. Assessment of disease activity (Simple Clinical Colitis Activity Index (SCCAI), Harvey Bradshaw Index (HBI)), IBD knowledge (CCKNOW), medication adherence (MMAS8), psychological distress (Hospital Anxiety and Depression Scale (HADS)), work productivity (WPAI) and quality of life (IBDQ) was performed to investigate any correlations between disease activity and PRO. Results: A total of 81 participants was included: 49% female, 57% Crohn disease (CD), 38% ulcerative colitis (UC) and 5% IBD‐unclassified, with a median age of 34 years. At least mild levels of depression were present in 21 of 81 (26%) of patients; 37 of 81 (46%) expressed some level of anxiety. A moderate‐to‐strong correlation was found between disease activity and depression in UC ( r = 0.84, P = 0.002) but not in CD ( r = 0.53, P = 0.29). Disease activity correlated with: overall work impairment due to health ( r = 0.85, P = 0.001), health‐related impairment while working ( r = 0.76, P = 0.02) and percentage of activity impaired due to health ( r = 0.83, P = 0.002) in UC only. Conclusions: Disease activity significantly affects mood and work productivity in patients with UC. Monitoring patients' ability to function and work, rather than minimising disease activity alone, should become a routine part of IBD care.